Form and Function of the Suffix -bel / -ble (< lat. -BῘLIS) in Post-Medieval Galician - Mariño Paz, Ramón (Madrygal. Revista de Estudios Gallegos, 2020)
After two previous papers about this suffix in Medieval Galician, in this article I gather information about its form and its function from the 16th century to the present day. Concerning the form, in Middle Galician (16-18th centuries) there is an almost absolute predominance of the variants with loss of the postonic vowel (-ble, -bre), while in Contemporary Galician (19th-21st centuries), even when these predominated, there was a revitalization of the Medieval variant -vel(e) (written -bel) that was consciously promoted by cultural and political Galicianism. Regarding its functional and semantic features, it should be noted that, as it happened in the Middle Ages, in the Middle and Contemporary Galician it continued to contend with others (-deiro, -dor, -tivo...) to express the active capacity, the semantic value it adopts when added to intransitive verbal bases.
Keywords: Post-Medieval Galician Language; Suffix -bel / -ble; Linguistic Purism